FORFEITED CAPITAL STOCK SUBSCRIPTIONS. - Homburger, Richard H. (The Accounting Review, 1949)
Abstract New Stock of a private corporation may be issued for cash or other consideration payable immediately or it may be offered for subscription, with the provision that payment is to follow at a later date. If a subscriber to capital stock does not pay for his shares at the time when such payment is due, his shares may be forfeited to the corporation, depending on the law of the state of incorporation, the provisions of the corporation's charter, and on the particular situation. Various accounting methods have been designed to record the transactions incidental to such forfeiture of stock subscriptions on the books of the issuing corporation; however, the treatment of these cases is not uniform. The main difficulty lies in the fact that statutory law largely governs the procedure for forfeiture of subscriptions and that the statutes of the different states contain different rules on the subject. This situation is further complicated in that some of these rules are open to different interpretations, in that certain questions of law have been decided differently by different courts even under the same statute. Finally, difference of opinion as to how far accounting procedure should be adapted to statutory rules may lead to different results.